Against a Theory of Meaning - Dennis Patterson (Washington University Law Quarterly, 1995)
Not only does linguistics fail to illuminate the meaning of legal texts, the approach to meaning taken by its practitioners is, philosophically speaking, nonsensical.' In the brief space of this article, I want to suggest why linguistics is a red herring on the trail to the meaning of legal texts.
Keywords: Linguistics